Influence of Approach Culturally Responsive Teaching Canva Helped with the Context of Regional Specialties on Students Interest in Learning and Learning Achievement in Social Sciences for Class VII Students SMP Maria Immaculata Cilacap - Shintia Hersiyani; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2025)
The use of technology in learning is very necessary in terms of designing, analyzing, evaluating, developing, and implementing material in the learning process. The important thing in the learning design process is the media used in learning. These learning media can be in the form of PowerPoint, digital modules, video tutorials, and other presentation materials. An educator should have learning media that is new and interesting in delivering material to his students, one of which is by presenting material through animated and fun learning videos. Canva is an application that can be used in designing learning media in the form of videos. How to use Canva Design is quite easy with many choices of design variations. This application provides a variety of design templates to use, ranging from free (free) to paid (pro). Canva can help users create and design a variety of creative designs, from designing brochures, advertisements, presentations, videos to infographics. This study aims to analyze the effectiveness of using the Canva application as a creative, innovative and collaborative learning video medium. The research method used is literature review. The method for searching for article data sources is carried out through the Google Scholar database resources (2020-2022) by taking relevant articles published in Indonesian. Key terms and phrases related to the Canva app, media, and learning videos were used in related subject searches. The results of the study show that the Canva application is effectively utilized as a medium for making creative, innovative and collaborative learning videos, so that it can assist educators in delivering material and make it easier for students to understand learning material. In addition, using Canva is also more efficient because it provides a variety of design templates for free and is available in several versions, namely web, Android and iPhone, so you can make learning videos simply by using your cellphone (gadget).